The multicellular interplay of microglia in health and disease: lessons from leukodystrophy - Woutje M. Berdowski; Leslie E. Sanderson; Tjakko J. van Ham (The Company of Biologists, 2021)
Microglia are highly dynamic cells crucial for developing and maintaining lifelong brain function and health through their many interactions with essentially all cellular components of the central nervous system. The frequent connection of microglia to leukodystrophies, genetic disorders of the white matter, has highlighted their involvement in the maintenance of white matter integrity. However, the mechanisms that underlie their putative roles in these processes remain largely uncharacterized. Microglia have also been gaining attention as possible therapeutic targets for many neurological conditions, increasing the demand to understand their broad spectrum of functions and the impact of their dysregulation. In this Review, we compare the pathological features of two groups of genetic leukodystrophies: those in which microglial dysfunction holds a central role, termed 'microgliopathies', and those in which lysosomal or peroxisomal defects are considered to be the primary driver. The latter are suspected to have notable microglia involvement, as some affected individuals benefit from microglia-replenishing therapy. Based on overlapping pathology, we discuss multiple ways through which aberrant microglia could lead to white matter defects and brain dysfunction. We propose that the study of leukodystrophies, and their extensively multicellular pathology, will benefit from complementing analyses of human patient material with the examination of cellular dynamics in vivo using animal models, such as zebrafish. Together, this will yield important insight into the cell biological mechanisms of microglial impact in the central nervous system, particularly in the development and maintenance of myelin, that will facilitate the development of new, and refinement of existing, therapeutic options for a range of brain diseases.